Konseling Pra-Nikah : Pentingnya Kesiapan Psikologis Sebelum Memasuki Kehidupan Pernikahan - Amalia Juniarly; Angeline Hosana Zefany Tarigan; Dewi Anggraini; Rachmawati (Universitas Muhammadiyah Palembang, 2024)
Premarital counseling is a guidance and consultation service provided to couples who are planning to get married. The main goal is to help couples to understand and prepare themselves for various aspects of marriage, so that they are better prepared to face challenges that may arise in married life. In this counseling, couples are invited to discuss important topics such as communication, finances, roles and responsibilities, values and expectations, how to manage conflict, and family planning. This activity is carried out using assessment, counseling, and case study methods. Based on the results of the counseling, it is known that overall, both MRR and VAI felt very satisfied (score 25 for both). Likewise with AY (score 24) and DF (score 23), they were also very satisfied with all aspects of their relationship, namely general satisfaction in the relationship; communication in the relationship; intimacy and emotional closeness; support and cooperation; conflict resolution; balance between personal life and relationships; and overall satisfaction with the current relationship. To strengthen the relationship, AY and DF have the same steps to improve communication and create a joint financial plan. While MRR and VAI have similar steps to improve communication and manage time for personal activities.